A comparison study of the echocardiographic changes in hypertensive patients treated with telmisartan vs. enalapril. (1st March 2017) - Hadi, Najah R; Abdulzahra, Mohammad S; Al-Huseini, Laith M; Al-Aubaidy, Hayder A
Abstract: Background: Hypertension-induced cardiac dysfunction is variable among different anti-hypertensive medications. This study compares the effects of telmisartan and enalapril on echocardiographic parameters in hypertensive patients. Materials and methods: This was a randomised single blinded study. Eighty hypertensive patients were included in this study and they were randomly allocated into two study groups: Group 1 included 40 patients who took telmisartan 80 mg once daily for six months. Group 2 included 40 patients who took enalapril, 20 mg once daily for six months. An additional 40 healthy participants were enrolled in the study as controls (Group 3). Baseline echocardiographic scan was done at the start of the study and after 6 months of treatment including assessment of left ventricular systolic and diastolic functions with assessment of left ventricular mass index, in addition to measurements of blood pressure, heart rate and double product. Results: Both group 1 and group 2 (telmisartan and enalapril groups respectively) showed comparable statistically significant improvement in the diastolic functional parameters (P < 0.010), while both medications didn't demonstrate changes in the systolic functional parameters. Furthermore, telmisartan was significantly effective in reducing the interventricular septal thickness and left ventricular mass index (P < 0.010). Conclusions: Both drugs interfere with renin–angiotensin aldosterone system, protecting the myocardium from high blood pressure. Findings from our study provide key results for physicians in deciding the appropriate antihypertensive drug for each patient depending based on the patient's intolerability for either medication.